The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.9734/irjpac/2013/4287
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Fly Ash by Thermal Activation: A DR/FTIR Study

Abstract: To acquire a deeper understanding of surface chemistry of fly ash along with thermal activation, the states of mineral phases, water and -OH groups on silica are studied in fly ash at different calcination temperatures by DR/FTIR spectroscopic technique. DR/FTIR spectroscopy allows differentiation of various types of bonds in a material on a molecular level. The spectroscopic results are also supported by XRF, XRD and SEM analysis. Studied fly ash was collected from Jamshedpur Thermal Power Station as an extre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…16 The heavy and trace metals present in fly ash can become more stable and inert beyond 800 C. 17 Katara et al reported the thermal surface activation of fly ash and also observed the color change, which is possibly due to the transformation of magnetite to hematite above 600 C. 18 …”
Section: Effect Of Beneficiationmentioning
confidence: 97%
“…16 The heavy and trace metals present in fly ash can become more stable and inert beyond 800 C. 17 Katara et al reported the thermal surface activation of fly ash and also observed the color change, which is possibly due to the transformation of magnetite to hematite above 600 C. 18 …”
Section: Effect Of Beneficiationmentioning
confidence: 97%
“…Results are supported by the findings of Sarkar et al (2006) that strong mineral bands (Si-O-Si= Si-O stretching) are observed at 1,031-1,095 cm À1 in all the fractions of Indian fly ash (magnetic=non-magnetic) that marks the presence of kaolinite, quartz, and mullite. The peak observed at 2,887 cm À1 and above could be assigned to C-H stretching vibration of organic contaminants or some hydrocarbon present in fly ash, whereas the peak observed at 3,096-3,553 cm À1 corresponds to O-H bonding (Katara et al 2013). Previous FTIR studies report that coal fly ash modified with humic substances could be evaluated for …”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 97%
“…The nonmagnetic fraction was calcinated for 2 h at 800 C to remove the unburnt carbon, unwanted organic salts, and to stabilize the trace elements present in fly ash. 19 The calcinated fly ash fraction obtained from the first stage was milled thorough highenergy planetary ball mill (PULVERISETTE, FRITSCH, Germany). Fly ash was milled for maximum of 60 h and samples were collected at every 20-h interval and analyzed for the size distributions and to optimize the milling parameters.…”
Section: Preparation Of Nfamentioning
confidence: 99%